Incidence and diversity of the fungal genera Aspergillus and Penicillium in Portuguese almonds and chestnuts - Rodrigues, Paula (2013)
Almonds (Prunus dulcis (Miller) D.A. Webb) and European (sweet) chestnuts (Castanea sativa Miller) are of great economic and social impact in Mediterranean countries, and some areas they constitute the main income of rural populations. Despite all efforts to control fungal contamination, toxigenic fungi are ubiquitous in nature and occur regularly in worldwide food supplies, and these nuts are no exception. This work aimed to provide knowledge on the general mycobiota of Portuguese almonds and chestnuts, and its evolution from field to the end of storage. For this matter, 45 field chestnut samples and 36 almond samples (30 field samples and 6 storage samples) were collected in Trás-os-Montes, Portugal. All fungi belonging to genus Aspergillus were isolated and identified to the section level. Fungi representative of other genera were identified to the genus level. In the field, chestnuts were mainly contaminated with the genera Fusarium, Cladosporium, Alternaria and Penicillium, and the genus Aspergillus was only rarely found, whereas almonds were more contaminated with Aspergillus. In almonds, Aspergillus incidence increased significantly from field to the end of storage, but diversity decreased, with potentially toxigenic isolates belonging to sections Flavi and Nigri becoming more significant and widespread throughout storage. These fungi were determined to be moderately associated, which can be indicative of mycotoxin co-contamination problems if adequate storage conditions are not secured.